2020
DOI: 10.1099/acmi.0.000114
|View full text |Cite
|
Sign up to set email alerts
|

Does salinity affect lifestyle switching in the plant pathogen Fusarium solani?

Abstract: Symbiotic microbes that live within plant hosts can exhibit a range in function from mutualistic to pathogenic, but the reason for this lifestyle switching remains largely unknown. Here we tested whether environmental stress, specifically salinity, is a factor that can trigger lifestyle switching in a fungus mainly known as a pathogen, Fusarium solani. F. solani was isolated from roots of Phragmites australis (common reed) in saline coastal marshes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It is difficult to pinpoint the exact reason for this, but environmental changes could be one of the driving factors behind it [ 166 ]. The environmental factors on lifestyle switching are generally coupled and discussed with the symbiotic fungi, which often live with plants by creating mutualistic relationships; however, they may change their lifestyle into a parasitic one [ 167 , 168 ]. In a study, Delaye et al [ 169 ] analyzed the lifestyle switching of endophytes, necrotrophs, and biotrophs.…”
Section: Plant–fungal Interactions Under the Changing Environmental C...mentioning
confidence: 99%
“…It is difficult to pinpoint the exact reason for this, but environmental changes could be one of the driving factors behind it [ 166 ]. The environmental factors on lifestyle switching are generally coupled and discussed with the symbiotic fungi, which often live with plants by creating mutualistic relationships; however, they may change their lifestyle into a parasitic one [ 167 , 168 ]. In a study, Delaye et al [ 169 ] analyzed the lifestyle switching of endophytes, necrotrophs, and biotrophs.…”
Section: Plant–fungal Interactions Under the Changing Environmental C...mentioning
confidence: 99%
“…soil pH, soil temperature, humidity, and nutrients [16]. Germination, timing germination and growth Fusarium decrease if land salinity increases [17].…”
Section: Resultsmentioning
confidence: 99%
“…This author further reported the production of sporangia by Phytopthora parasitica and P. citrophthora (an important citrus pathogen) increased in salt affected soils. According to Eydoux and Farrer (2020), increasing salinity slightly influenced the pathogenicity of Fusarium solani in rice (Oryza sativa). Dikilitas (2003) reported that, disease progress in tomato inoculated with Verticillium albo-atrum under salinity stress accelerated due to effect of salinity.…”
Section: Effects Of Salinity On Plant Pathogensmentioning
confidence: 99%